Solar Home System Plant Menggunakan Gabungan Dari DVD dan Solar Panel - Kresna Adi Prasetya; Arwizet K; Yolli Fernanda; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
Indonesia is a tropical country that has great potential for harnessing and managing solar energy. At present, the technology of converting solar energy into electrical energy such as solar cells still has weaknesses in terms of cost. Therefore, this study aims to test the potential of solar energy by creating a solar home system plant using DVD and Zener diode. This solar home system plant using DVD has the advantage of using low cost and the power generated can be said to be sufficient. In addition, this product can be used as a substitute for solar cells if properly applied. This study uses an experimental method in a quantitative approach. In this study, the independent variable is the structure of the solar panel while the dependent variable is the amount of energy read by the voltmeter. This study uses the photoelectric principle. Where photoelectricity is an electron released from the surface of an object exposed to light. This study was carried out by looking at how much power could be generated by DVD and Zener diode. The results showed that DVD and Zener diode can generate electrical energy, but the results are still too small and a large number of DVDs are needed to generate more energy. So it can be concluded that DVD still cannot replace solar panels, but can be used as a tool to maintain the stability of solar panels.